Multicriteria analysis in planning roads – Part 2. Methodology for selecting the optimal variant of the road - P. Żabicki; W. Gardziejczyk (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2020)
The article presents the methodology for selecting the optimal variant of the road on a regional level. The suggested methodology is based on a combination of criteria value normalization method and the variant assessment method. Based on survey studies conducted using the Delphi method, a starting list of criteria was designed and the significance of the individual groups of main criteria and sub-criteria was determined. The final assessments of the analysed variants are calculated based on the aggregation of the marks obtained for the normalization and assessment methods. The methodology can be divided into six stages: determining the variants for analysis, selecting the variant assessment criteria, creating the assessment matrix, normalizing criteria value, using the variant assessment method, variant ranking. The methodology was tested on the examples of planning a bypass of Mazury and Księżyno towns as a part of Regional Road 678 in Poland.